(untitled) (International relations and international law Journal, 2016)
One of the key pillars of the multilateral relations between states is their economic component. Undoubtedly an important factor in relations between the Republic of Kazakhstan and the Russian Federation is the mutual trade, financial cooperation. Kazakhstan and Russia have a common national economic and military-industrial complexes. After the collapse of the USSR a significant part of the connection was lost, forcing the country to re-create a common economic space. In addition to creating the CIS in 1995, countries agreed to create a common economic zone – the Customs Union. Since 2010 all economic relations between the two states can be viewed through the prism of already existing Customs Union. The results of three years under the banner of the organization are analyzed and a prediction based on current information are made.